ETF Sampling and Index Arbitrage - Brogaard, Jonathan; Heath, Davidson; Huang, Da (Journal of Financial and Quantitative Analysis, 2026)
Abstract This article shows that exchange-traded funds (ETFs) “sample” their indexes, systematically underweighting or omitting illiquid index stocks. As a result, arbitrage activity between the ETF and its index has heterogeneous effects on underlying asset markets. Using an instrumental variables approach, we find that the trading activity of ETFs reduces liquidity and price efficiency and increases volatility and co-movement for liquid stocks but has no effect on illiquid stocks. Our results demonstrate that the effects of passive investing on asset markets depend on how passive funds replicate their target index.